An ambiguous journey to the city the village and othe[r] odd ruins of the self in the Indian imagination - Nandy, Ashis (New Delhi ; Oxford : Oxford University Press, 2007)
Ashis Nandy tells the story of an apparently territorial journey, between the village and the city, to capture some of the core fantasies and anxieties of the Indian civilization in the past hundred years.
Originally published: 2001.
Description based on online resource; title from PDF title page (viewed on July 16, 2012).
Includes bibliographical references and index.
Keywords: India -- Civilization -- 1947-